A new Gammagraphic and Functional-Based Classification for Hyperthyroidisms - Sanchez Beorlegui, Jesús (2000)
OBJECTIVE: The absence of an universal classification for hyperthyroidisms (HT), give rise to inadequate interpretation of series and trials, and prevents decision making. We offer a tentative classification based on gammagrafic and functional findings. MATERIAL AND METHODS: Clinical records from patients who underwent thyroidectomy in our Department since 1967 to 1997 were reviewed. Those with functional measurements of hyperthyroidism were considered. All were managed according to the same preestablished guidelines. RESULTS: HT was the surgical indication in 694 (27,1%) of the 2559 thyroidectomies. Based on gammagraphic studies, we classified HTs in: Parenchymatous Increased-Uptake, which could be Diffuse, Diffuse with Cold Nodules or Diffuse with at least one Nodule, and Nodular Increased-Uptake (Autonomous Functioning Thyroid Nodes [AFTN]), divided into Solitary AFTN or Toxic Adenoma and Multiple AFTN o Toxic Multinodular Goiter. CONCLUSIONS: This gammagraphic - based classification is useful and has high sensitivity to detect these nodules assessing their activity, allowing us to make therapeutic decision making and, in some cases, to choose surgical technique.